Design creativity, technical execution and aesthetic appeal: a CAT with caveats (Part 2). Issue 1 (3rd April 2018) - Jeffries, K. K.; Zamenopoulos, T.; Green, A. J. K.
Abstract: This study explores to what extent technical execution and aesthetic appeal may be related to assessments of graphic design creativity. These new research findings build upon Jeffries' 2017 publication in the International Journal of Design Creativity and Innovation, and further underpin the caveats identified in relation to the Consensual Assessment Technique (CAT). Eight professional graphic designers rated thirty-two artworks for a creative typographical task. Individual artworks were created by novices who had no experience of graphic design, through to professional graphic designers with 35 years of full-time experience. Written instructions to judges emphasised artwork be rated on creativity-only (without considering technical execution or aesthetic appeal), and this 'creativity-only' feature was verbally re-emphasised to judges by the researcher. Inter-rater agreement for creativity was a Cronbach's alpha of .92; considerably higher than in previous studies, with implications that may relate to the use of the CAT as a measure of design creativity more broadly, and beyond graphic design.